EXPLORING STUDENTS’ DIFFICULTIES IN READING USING QUESTION AND ANSWER RELATIONSHIP - Miftah Fauzi; Yanuarti Apsari (PROJECT (Professional Journal of English Education), 2022)
The aim of the research is to identify students' difficulties in reading using Question-Answer Relationship. The researchers employed descriptive qualitative research. The participants of the research were seventh-grade students of SMPN 2 Parongpong. To collect data for this study, questionnaire and test were used as the instruments of this research. Then, the data were analyzed qualitatively. The data of the research showed that the students faced several difficulties in reading deal with lack of vocabulary, difficulty in determining main ideas and finding specific information. Keywords:  Sudents’ Difficulties, Question Answer Relationship, Reading